The Potential Of H'FRES V:1.0 (High Supersonic Frequency) For Locust Elimination - Naagasurune, Arumugam (2022)
The characteristics of a sustainable development evaluation are being developed within the context of green technology. As agriculture continues to be chastised for its negative environmental impact, resource efficiency and clean technology adoption become increasingly critical. Furthermore, there are several technical solutions available to help "green" agriculture to solve its difficulties, whether by reducing inputs, generating renewable energy, or maintaining ecosystems. Due to the wide range of options, difficulty in cost-benefit analyses, and potential trade-offs in sustainability, clean technology and sustainable development selections remain complicated. It is time to utilize current technology to overcome environmental issue (Fraser, A, 2019). In many parts of the world, desert locust plagues may be a major contributor to famines and a danger to food security. The 1986–1989 Desert Locust epidemic, as well as other upsurges over the last two decades, indicate the ancient pest's continued ability to endanger agriculture and livelihoods throughout wide swaths of Africa, the Near East, and South West Asia. A strong rise in 2004–2005 resulted in massive crop losses in West Africa, putting the region's food security at risk. Locusts are one of the most harmful pests in agriculture. They are a hemimetabolous group of short-horned grasshoppers belonging to the Acrididae family. When a swarm of grasshoppers congregates, they have a unique tendency of altering habits and behaviours, which is stimulated by many environmental conditions (FAO, 2016). The goal of this study is to assess sophisticated sound sensor techniques and technology advancement for autonomous detection and monitoring of insect pests. Instead of using pesticides, the government should support the use of biological agents and specific insects, among other means of insect pest management. The proposed sparkling locusts destroy the framework while causing no harm to people. Individuals are unaffected by this framework because it creates high supersonic frequency sound waves. High supersonic frequency sound waves with a repetition scope of over 20 kHz are inaudible to humans. When locusts and other creepy crawlies congregate, they are continually aware of high supersonic frequency sound waves, which aggravates them and forces them to flee the area. The purpose of this study was to determine as effective H'FRES V:1.0 was in reducing locust populations and how well a 12-volt battery could power an LED strip light. The H'FRES V:1.0 is a mechanised pesticide control device that is an innovative solution that eliminates pesticide contamination and can contribute to the long-term growth of agricultural products. H'FRES V:1.0 employs contemporary microelectronics technology to act directly on the auditory neural system of locust’s insects, causing their physiological system to become disturbed, irritated, lose appetite, and eventually die. With various ranges, the potential of high supersonic frequency for locust insect removal has been assessed. The sound sensor with Arduino continually generates sound waves in various frequency bands, preventing locusts from adapting to their living habitat, which may cause them to get dizzy and increase their chances of being killed. A 20-watt solar cell provides electrical energy to the battery charging mechanism for use at night. Furthermore, the LED bulb will automatically turn off the night light at dawn and turn it on again at dusk. During the day, however, the insects will fly towards the product because they believe it is their predator. When there is no sunlight, this designed H'FRES V:1.0 has an automatic control system that attracts insect pests and shuts off when the sun shines. The suggested H'FRES V:1.0 attracted a variety of locust pests in agriculture, according to the findings of the system installation test. The suggested H'FRES V:1.0 system consumes less energy while maintaining reasonable cost, availability, and flexibility. The Arduino IDE, which is used to write embedded code for the Arduino board, was utilised as the software tool. The designed gadget uses very little power and has the potential to effectively repel locusts in lawns and other environments. As a conclusion, H'FRES V:1.0 may be employed in the agricultural, pesticide, and natural science industries, with an emphasis on R&D, manufacturing, and distribution. The proposed system will be implemented.